1992
DOI: 10.1007/bf01962068
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic sensitivity of theBacteroides fragilis group in Europe

Abstract: Rates of resistance to 12 antibiotics were determined for 1,289 isolates of Bacteroides fragilis group submitted in 1988-1989 by 22 laboratories in 15 European countries. There was no resistance to metronidazole (breakpoint 8 mg/l) and only one isolate was resistant to chloramphenicol (breakpoint 8 mg/l). Resistance was uncommon for imipenem (0.3% at greater than 4 mg/l), amoxicillin/clavulanate (1% at greater than 8 mg/l), cefoxitin (3% at greater than 32 mg/l), mezlocillin (6% at greater than 64 mg/l) and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
35
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 14 publications
6
35
1
Order By: Relevance
“…In previous studies, B. ovatus and then B. fragilis were the most frequently isolated anaerobic resistant strains from intestinal microfloras (1,12). The antimicrobial susceptibility of the B. fragilis group in the present study correlates well with those found in recent investigations in Canada and Europe (12,16).…”
Section: Discussionsupporting
confidence: 89%
“…In previous studies, B. ovatus and then B. fragilis were the most frequently isolated anaerobic resistant strains from intestinal microfloras (1,12). The antimicrobial susceptibility of the B. fragilis group in the present study correlates well with those found in recent investigations in Canada and Europe (12,16).…”
Section: Discussionsupporting
confidence: 89%
“…Since therapy for anaerobic infection is often required before the results of susceptibility tests are available and regional differences in resistance patterns have been well documented (2,3,4,20,21), the results of periodic susceptibility studies are useful as a guide in the empiric choice of agents for a correct treatment. This study confirms the reports of other investigators (20,21) that the following drugs are active against the majority of Bacteroides fragilis strains: metronidazole, imipenem and the combination of a betalactam drug and a beta-lactamase inhibitor such as amoxicillin/clavulanate.…”
Section: Discussionmentioning
confidence: 99%
“…Among anaerobes pathogenic for humans, Bacteroides fragilis is the member most commonly encountered clinically (1), In recent years the literature has reported an increasing resistance of Bacteroidesfragilis to antimicrobial agents as well as differences in the rates of resistance among strains isolated in different geographical areas (2)(3)(4). Therefore, periodic surveillance using simple and reliable methods is essential for the knowledge of resistance patterns in any specific country.…”
mentioning
confidence: 99%
“…From resistance surveillance it is known that species determination may be extremely important for routine laboratories in the case of Bacteroides isolates, as significant differences in resistance rates to antibiotics can be observed among the different species (Snydman et al, 2007;Phillips et al, 1992;Hedberg et al, 2003;Nagy et al, 2011b). On the other hand, only B. fragilis isolates belonging to division II can harbour the cfiA gene, responsible for carbapenem resistance.…”
Section: Discussionmentioning
confidence: 99%